Le guarani dans la poésie bilingue : renégocier les notions d’exception et de marginalité - Manon Naro (Caravelle)
This article seeks to explore the circumstances of the rising as well as the features of bilingual poetry in guarani, considering the concepts of marginality and exception. By analysing the discourse about Paraguayan literature and studying several contemporary bilingual poetry books, we shall try to perceive how the story of this poetry is constructed and reconstructed, from the stigma of marginality and exception to the renegotiation of these notions aiming to build a poetry of the resistance.